2002
DOI: 10.1046/j.1440-1584.2002.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Current health scenario in rural India

Abstract: India is the second most populous country of the world and has changing socio-political-demographic and morbidity patterns that have been drawing global attention in recent years. Despite several growth-orientated policies adopted by the government, the widening economic, regional and gender disparities are posing challenges for the health sector. About 75% of health infrastructure, medical man power and other health resources are concentrated in urban areas where 27% of the population live. Contagious, infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 2 publications
1
64
1
Order By: Relevance
“…In our sample there were also increased numbers of concurrent sex partners amongst tribals, most often with CSWs, and a trend towards increased numbers of lifetime sex partners. While there was not an increase in HIV infection amongst tribals, HIV is now prevalent within this component of the caste system and may be further exacerbated by the continued lack of shift of health preventive resources from urban to rural areas (Patil et al, 2002). It is important to note, however, that tribals are a heterogeneous population even within this study's 'Banjara' sub-group, and sexual matching patterns and risk for HIV infection may differ between tribal sub-groups.…”
Section: Discussionmentioning
confidence: 71%
“…In our sample there were also increased numbers of concurrent sex partners amongst tribals, most often with CSWs, and a trend towards increased numbers of lifetime sex partners. While there was not an increase in HIV infection amongst tribals, HIV is now prevalent within this component of the caste system and may be further exacerbated by the continued lack of shift of health preventive resources from urban to rural areas (Patil et al, 2002). It is important to note, however, that tribals are a heterogeneous population even within this study's 'Banjara' sub-group, and sexual matching patterns and risk for HIV infection may differ between tribal sub-groups.…”
Section: Discussionmentioning
confidence: 71%
“…Seventy-five percent of India's population lives in rural and village districts where access to health care is extremely limited, particularly for emergency services [1]. The current health state for Indians living in these locations is a cause for grave concern.…”
Section: Introductionmentioning
confidence: 99%
“…The current health state for Indians living in these locations is a cause for grave concern. Although infectious and contagious diseases, compounded by poverty and malnutrition, predominate in these regions as the major cause of morbidity and mortality, HIV/AIDS, cancer and road-traffic injuries have risen dramatically [1]. In India, death occurs due to road-traffic injuries every two minutes [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vegetarian population of India, daily consumption of vegetables has been a traditional practice. Still the prevalence of hypertension in Indians is increasing [6,7], indicating the existence of different risk factors. Several studies on risk factors of hypertension in Indians have reported demographic, anthropometric, lifestyle factors, blood lipid profile or glucose [8,9].…”
Section: Introductionmentioning
confidence: 99%